Singularity robust trajectory generator for robotic manipulator based on genetic algorithm with dynamic encoding of solutions - Gierlak, Piotr (Advances in Mechanical and Materials Engineering, 2018)
In this paper a singularity robust trajectory generator for robotic manipulators is presented. The generator contains the procedure of solving the inverse kinematics problem. This issue is defined as an optimization problem, where a genetic algorithm is used for optimizing the fitness function. In order to avoid singularity problem, the generator is based on the direct kinematics problem. The trajectory generator allows to obtain generalized coordinates, velocities and accelerations. Simulation results show that the procedure generates a trajectory of manipulator even in kinematics singularities.